Diagnostic accuracy of point-of-care tests in acute community-acquired lower respiratory tract infections. A systematic review and meta-analysis. (January 2022) - Gentilotti, Elisa; De Nardo, Pasquale; Cremonini, Eleonora; Górska, Anna; Mazzaferri, Fulvia; Canziani, Lorenzo Maria; Hellou, Mona Mustafa; Olchowski, Yudith; Poran, Itamar; Leeflang, Mariska; Villacian, Jorge; Goossens, Herman; et al.
Abstract: Background: Point-of-care tests could be essential in differentiating bacterial and viral acute community-acquired lower respiratory tract infections and driving antibiotic stewardship in the community. Objectives: To assess diagnostic test accuracy of point-of-care tests in community settings for acute community-acquired lower respiratory tract infections. Data sources: Multiple databases (MEDLINE, EMBASE, Web of Science, Cochrane Library, Open Gray) from inception to 31 May 2021, without language restrictions. Study eligibility criteria: Diagnostic test accuracy studies involving patients at primary care, outpatient clinic, emergency department and long-term care facilities with a clinical suspicion of acute community-acquired lower respiratory tract infections. The comparator was any test used as a comparison to the index test. In order not to limit the study inclusion, the comparator was not defined a priori. Assessment of risk of bias: Four investigators independently extracted data, rated risk of bias, and assessed the quality using QUADAS-2. Methods of data synthesis: The measures of diagnostic test accuracy were calculated with 95% CI. Results: A total of 421 studies addressed at least one point-of-care test. The diagnostic performance of molecular tests was higher compared with that of rapid diagnostic tests for all the pathogens studied. The accuracy of stand-alone signs and symptoms or biomarkers was poor. Lung ultrasound showed high sensitivity and specificity (90% for both) for the diagnosis of bacterial pneumonia. Rapid antigen-based diagnostic tests for influenza, respiratory syncytial virus, human metapneumovirus, and Streptococcus pneumoniae had sub-optimal sensitivity (range 49%–84%) but high specificity (>80%). Discussion: Physical examination and host biomarkers are not sufficiently reliable as stand-alone tests to differentiate between bacterial and viral pneumonia. Lung ultrasound shows higher accuracy than chest X-ray for bacterial pneumonia at emergency department. Rapid antigen-based diagnostic tests cannot be considered fully reliable because of high false-negative rates. Overall, molecular tests for all the pathogens considered were found to be the most accurate.